To solve the equation -6x + 7 = 3(2x - 3) - 4(-10 + 4x), we need to simplify both sides of the equation and then isolate the variable x.
First, distribute the 3 and 4 on the right side:
-6x + 7 = 6x - 9 + 40 - 16x
Combine like terms:
-6x + 7 = -10x + 31
Add 10x to both sides to isolate the x term:
4x + 7 = 31
Next, subtract 7 from both sides:
4x = 24
Finally, divide both sides by 4 to solve for x:
x = 6
Therefore, the solution to the equation -6x + 7 = 3(2x - 3) - 4(-10 + 4x) is x = 6.
-6x+7=3(2x-3)-4(-10+4x)
1 answer